An Interpretation of Rawls’ “Kantian Interpretation - Chaly, Vadim (Con-Textos Kantianos. International Journal of Philosophy, 2015)
Calling Kant a liberal philosopher requires important qualifications. Much like his theoretical philosophy, his political transcendentalism was and remains a great enterprise of navigating between the extremes of liberalism and conservatism, of balancing the “empirical” and the “pure” in human society, as well as in human mind. Of all the attempts to enlist Kant among the classics of liberalism, John Rawls’ is the most impressive and thorough. However, it is hardly a success. The reason for this lies in a profound difference in their answering the fundamental (and therefore vague) question “What is Man?”. This paper is an attempt to revise the debate about the extent of Rawls’ Kantianism and to compare the meanings of basic concepts of what could be called “pure political anthropology” in Kant and in Rawls.